Feasibility and clinical decision-making with 3D echocardiography in routine practice. Issue 4 (30th July 2007) - Hare, J L; Jenkins, C; Nakatani, S; Ogawa, A; Yu, C-M; Marwick, T H
Abstract : Objective: To assess the feasibility and potential impact of routine three-dimensional (3D) echocardiographic assessment of left ventricular (LV) ejection fraction and volumes on clinical decision-making. Methods: Patients referred to three hospital-based echocardiography laboratories underwent 2D echocardiography (2DE) and 3D echocardiography (3DE). Feasibility was assessed in a group of 168 unselected patients and decision-making assessed within an expanded group of 220 patients. The time for acquisition and measurement was obtained. Feasibility was defined by ability to measure LV parameters. The potential of 3DE to alter clinical decisions based on 2DE was evaluated by the ability to identify four clinically relevant measurement thresholds: (1) LV end-systolic volume (LVESV) >50 ml/m 2 (indication for surgery in regurgitant valve disease); (2) LVESV >30 ml/m 2 (prognosis after infarction); (3) LV ejection fraction (LVEF) <35% (indication for implantable defibrillator); and (4) LVEF <40% (indication for heart failure treatment). Results: 3DE was technically feasible in 83% of unselected patients. The additional time for 3D acquisition and measurement was available in 184 patients and was 5.4 (SD 2.0) minutes. The use of 3DE changed categorisation in between 6–11% of patients. Within threshold categories, 3D reallocated 17.5% (11/63) of patients with LVEF <35%, 16.1% (13/81) for LVEF <40%, 12.4% (13/105) for LVESV >30 ml/m 2 and 8.5% (5/59) for LVESV >50 ml/m 2 . Most of the impact of 3D was within 10 ml/m 2 of selected volume thresholds (⩾75%) and 10% of EF thresholds (>80%). Conclusion: Measurement of LV volumes and EF by 3DE is clinically feasible and has the potential to significantly alter clinical decision-making.